ANALISIS PENGGUNAAN INFORMASI DAN PENERAPAN AKUNTANSI MANAJEMEN TERHADAP STRATEGI PENGEMBANGAN UMKM KOTA BONTANG - Eqy Refiyanto; Dul Muid (Diponegoro Journal of Accounting, 2022)
MSME is an economic sector that able to reinforce the Indonesian economic state with government support. With the existence of MSME, Indonesian people can develop their entrepreneurial independence and also explore the opportunities to increase their income. This study aims to explain and analyze the use of information and the application of management accounting strategies for the development of Micro, Small, and Medium Enterprises (MSME) located in Bontang City. This study uses a qualitative descriptive approach, namely measurement based on the phenomenon or reality which is the objects of research. The data used in this study are primary data from questionnaires which collected from 60 respondents of MSMEs in Bontang. There are two main stages of research. First, identify and analyze the use of information and the application of MSME accounting management in Bontang City. Second, explain the strategies applied by MSMEs in Bontang City as a discussion and make the final conclusions. The results of this study indicate that some MSMEs in Bontang City still not fully understand the management accounting information correctly. Therefore, MSME still apply the manual bookkeeping method. Some other MSMEs have overcome and applied the management accounting information properly.